2000
DOI: 10.1094/cchem.2000.77.6.724
|View full text |Cite
|
Sign up to set email alerts
|

Solvent Extraction of Zein from Dry‐Milled Corn

Abstract: Batch extraction of zein from dry‐milled whole corn with ethanol was optimum with 70% ethanol in water, an extraction time of 30–40 min, and temperature of 50°C. High yields (60% of the zein in corn) and high zein contents in the extracted solids (50%) were obtained at a solvent‐to‐solids ratio of 8 mL of 70% ethanol/g of corn. However, zein concentration in the extract was higher at lower ratios. Multiple extraction of the same corn with fresh ethanol resulted in a yield of 85% after four extractions, whereas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
40
0
3

Year Published

2006
2006
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(43 citation statements)
references
References 10 publications
0
40
0
3
Order By: Relevance
“…A maioria desses processos tem por base o uso de soluções alcoólicas, de baixa polaridade, empregadas como solventes. Segundo determinações de Shukla et al [16] , as maiores eficiências de extração de zeínas foram obtidas fazendo uso de etanol concentrado como solvente, considerando que a fração solúvel em álcool constitui na maior parte (80-90%) das proteínas presentes no milho, e a restante fracamente solúvel em álcali [17] . Adotamos neste trabalho a sequencia de extração desenvolvida por Forato [18] a partir do glúten de milho, processo esse em corrente uso na unidade da Embrapa Instrumentação.…”
Section: Processo De Extração Das Zeínasunclassified
“…A maioria desses processos tem por base o uso de soluções alcoólicas, de baixa polaridade, empregadas como solventes. Segundo determinações de Shukla et al [16] , as maiores eficiências de extração de zeínas foram obtidas fazendo uso de etanol concentrado como solvente, considerando que a fração solúvel em álcool constitui na maior parte (80-90%) das proteínas presentes no milho, e a restante fracamente solúvel em álcali [17] . Adotamos neste trabalho a sequencia de extração desenvolvida por Forato [18] a partir do glúten de milho, processo esse em corrente uso na unidade da Embrapa Instrumentação.…”
Section: Processo De Extração Das Zeínasunclassified
“…CGM has low price and is used mainly for animal feeding (Dickey & Parris, 2001;Landry, 1997). However zein is an expensive product and thus extraction of zein and production of biodegradable film from it, would produce important economic benefits (Landry, Drihaye, & Damerval, 2002;Shukla, Cheryan, & Devor, 2000). Zein has excellent film forming properties and can be used for fabrication of biodegradable films.…”
Section: Introductionmentioning
confidence: 99%
“…However, the temperature should not be increased indefinitely since higher temperatures cause protein denaturation. Shukla et al (2000) also studied the effect of temperature on the extraction of proteins (zeins) from corn. They found that zein solubilization in the range of 20 to 60°C was highest at 50°C.…”
Section: Effects Of Operational Variables On Rhproinsulin Extractionmentioning
confidence: 99%